A relação entre os preditores clima de segurança, espiritualidade e comprometimento organizacional com a cultura de segurança - Almeida, Eberson Cordeiro de (My University, 2023)
The research investigates the relationship between safety climate, spirituality, and organizational commitment to the culture of safety at work. The goal is to fill a theoretical gap in this area and help organizations reduce the damage caused by workplace accidents. The bibliometric analysis revealed the originality of the proposed study. Research can help companies improve their occupational health and safety programs, promote employee communication and engagement, increase organizational commitment, and promote employee health and well-being. The sample consisted of 244 collaborators who answered a questionnaire with closed Likert-type items. The data were processed and analyzed using Microsoft Excel 2019 and Jamovi software. Of the 244 questionnaires, 237 were validated. Statistical analyses were performed, such as exploratory factor analysis, descriptive statistics, analysis of variance and linear regression. The results showed statistically significant correlations between the dimensions studied, with a significance level of p < 0.001. The coefficient of variation indicated a homogeneous distribution of the data, with values below 30%. The regression model revealed that 67% of the variability of the dependent variable (organizational commitment) can be explained by the predictors (spirituality, safety climate and safety culture). The company is currently at a stage of maturity of the bureaucratic security culture, with a tendency towards a proactive approach. [resumo fornecido pelo autor]
A pesquisa investiga a relação entre clima de segurança, espiritualidade no trabalho e comprometimento organizacional com a cultura em segurança no trabalho. O objetivo é preencher uma lacuna teórica nessa área e ajudar as organizações a reduzir os danos causados por acidentes de trabalho. A análise bibliométrica revelou a originalidade do estudo proposto. A pesquisa pode auxiliar as empresas a melhorar seus programas de saúde e segurança no trabalho, promover a comunicação e o envolvimento dos funcionários, aumentar o comprometimento organizacional e promover a saúde e o bem-estar dos funcionários. A amostra consistiu em 244 funcionários que responderam a um questionário com itens fechados do tipo Likert. Os dados foram tratados e analisados usando os softwares Microsoft Excel 2019 e Jamovi. Dos 244 questionários, 237 foram validados. Foram realizadas análises estatísticas, como análise fatorial exploratória, estatística descritiva, análise de variância e regressão linear. Os resultados mostraram correlações estatisticamente significativas entre as dimensões estudadas, com um nível de significância de p < 0,001. O coeficiente de variação indicou uma distribuição homogênea dos dados, com valores abaixo de 30%. O modelo de regressão revelou que 67% da variabilidade da variável dependente (comprometimento organizacional) pode ser explicada pelos preditores (espiritualidade no trabalho, clima de segurança e cultura em segurança). A empresa encontra-se atualmente em um estágio de maturidade da cultura de segurança burocrático, com tendência para uma abordagem proativa. [resumo fornecido pelo autor]
Keywords: Segurança do Trabalho; Espiritualidade; Ciências sociais; Ambiente de trabalho; Industrial safety; Spirituality; Social sciences; Work environment